(untitled) (Research, Society and Development, 2021)
Peri-implantitis is an inflammatory process that affects the tissues around an osseointegrated implant in function, resulting in the loss of the supporting bone. An acceptable cleaning technique must be able to debrid and detoxify the surface without traumatizing it. Therefore, the objective of the present scope review is to assess whether ozone therapy is effective in the treatment of peri-implantitis. For this, the study used the acronym PICOS. Pre-clinical in vivo studies in humans and clinical studies that evaluated the effectiveness of treating peri-implantitis with ozone were included. The searches were carried out in the PubMed, Embase, Scopus and Cochrane Library databases, and as a gray literature, a Google Scholar search was performed. The search strategy “" Ozone "AND (" Peri-Implantitis "OR" Dental Implants "OR" Peri-implant ")" was used. The reference management was performed using the EndNote Basic reference manager software. The Cochrane tool was used to assess the risk of bias in the studies that were included. The results of all studies were described in a narrative manner. This review included three articles. It was possible to see a significant reduction in all clinical parameters analyzed in the ozone group, except for the mucosal recession, which showed no or minimal improvement. Through the results of this review, it was possible to conclude that ozone therapy has great potential for the treatment of peri-implantitis, despite the high heterogeneity and the low quality of the inserted studies do not allow high quality evidence.